Catalisadores de Fe2O3, NiO e Fe2O3 - NiO Suportados in situ em Ce0,5Zr0,5O2 e Ce0,2Zr0,8O2 – Avaliação na Redução de NO com CO - Souza, Bruna Gonçalves de (Universidade Federal de São Carlos, 2014)
The increasing use of fossil fuels in combustion enginees and power generation plants has caused a large increase in the emission of sulfur oxides, nitrogen oxides (NOx) and carbon monoxide into the atmosphere which creates serious environmental problems. Catalytic processes are used in the abatement of NOx and a promising alternative is the reduction of NOx using CO as reducing agent on catalysts containing supported transition metal oxides. Taking this into account, the aim of this study was to prepare catalysts based on Fe2O3, NiO or Fe2O3-NiO supported on ceria-zirconia (molar ratios Ce:Zr equal to 1:1 and 1:4), incorporating the metal precursor salt in the sun of the support (in situ addition). The results of XRD data, Rietveld refinement and TEM indicated the formation of a solid solution CeO2-ZrO2 with cubic structure fluorite type; furthermore, it was not observed diffraction peaks of intense X-ray of Fe or Ni oxide as a consequence of a proper distribution of these oxides in the supports. The addition of Fe2O3 and/or NiO led to a decrease of the average crystallite size, causing an increase in SBET of the catalysts compared to the pure support. N2 physisorption measurements showed that the catalysts showed significant mesoporosity, which was attributed to the addition of Tween 80 during the sol-gel preparation, moreover, RTPH2 results confirm that the Fe2O3 reduction occurs at lower temperatures in the presence NiO. In addition, the catalysts showed satisfactory performance in the reduction of NO to N2 with CO, suggesting that the sol-gel method is adequate in their preparation. Furthermore, the catalyst 0,90Fe - 1Ce:1Zr reached the highest values of CO conversion to CO2 and NO to N2 at lower temperatures. The Fe2O3 catalysts were more selective to N2 formation compared to those containing NiO. In conclusion, the conversion NO to N2 was significantly affected when in contact with O2 and H2O interferences; however, this conversion did not change significantly in the presence of SO2. The catalysts showed a more significant reduction in conversion of NO to N2 when evaluated in the simultaneous presence of O2, SO2 and H2O.
Keywords: Catálise; Síntese; Sol-Gel; Redução de NO; NiO; Fe2O3; CeO2-ZrO2; Redução de NO a N2; Sol-gel in situ; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::FISICO-QUIMICA ORGANICA